Molestias producidas por el tratamiento de ortodoncia en estudiantes de la carrera de odontología de uniandes: un estudio descriptivo - Tamayo Aguirre, Karina Michelle (2025)
Introduction: Orthodontics is a process that involves the use of specific devices that can cause various physical and emotional discomforts in patients. It is important to understand that orthodontics is a specialised branch of dentistry that is dedicated to correcting dental malpositions and jaw problems. Objective: Therefore, the aim of this research was to analyse the prevalence and intensity of discomfort caused by orthodontic treatment in dental students at UNIANDES. Method: A survey of 7 questions with 8 sub-levels was used to evaluate the most frequent discomfort produced in the respondents by the use of dental treatment. Results: It was found that respondents experience discomfort when eating and enjoying their food, cleaning or brushing their teeth, and enjoying contact with people. These discomforts occurred once a month or every 15 days, being more frequent in patients with less than 6 months of treatment. In addition, significant differences were observed in the response to these discomforts depending on gender, type and time of treatment. Conclusion: According to the results obtained, the main discomforts suffered by the participants were identified as problems with eating and enjoying food (54.6%), cleaning or brushing teeth (61%), doing all work or socializing in a normal way (56.7%) and enjoying contact with people (55.3%). The frequency of these discomforts and the relationship between treatment and factors such as gender, time of use and type of treatment were also determined.